Coping Of Pre-Release Women's Prisoners - Nurul Laili; Megah Andriany; Anggorowati Anggorowati; Ainul Yaqin Salam (Alma Ata University Press, 2019)
Coping of women's prisoners could changed in various conditions, one of them when they were in pre release condition. Various kinds of coaching has been done, however, did not close possibility of maladaptive coping still found on women's prisoners pre release. The aim of this study was to identity the coping of women's prisoners pre release in Prison.This study used quantitative descriptive. The number of samples in this study were 26 women's prisoners pre-release. Sampling by purposive sampling technique. The data were compiled with a Ways of Coping Scale questionnaire according to Lazarus and Folkman (1984) consisting of 60 statements divided into two types, namely 20 emotion-focused coping statements and 40 problem-focused coping statements. This study was conducted in one of the Prison in Indonesia. The analysis of this study used univariate and frequency distribution. The results showed that women's prisoners who used emotion-focused coping as much as 57.69% in passable category and 42.31% have poor category. While respondents who used problem-focused coping as much as 7.69% in good category, 84.62% passable and 7.69% poor category.Based on the results of this study, it could be concluded that women's prisoners pre release used both types of coping and majority of respondents were categorized as good enough and less good. Women's prisoners who had passable coping category risky lead for poor coping and poor coping could lead to maladaptive coping, so that they could harm himself and others.Therefore, it was necessary to do deeper screening of coping women's prisoners pre release.The results of this study could be used as a reference in determining the appropriate intervention for preparation of women's pre release and return to the community. Keywords: coping, prisoners, Women, pre release